(untitled) (EAAE Annual Conference Proceedings, 2020)
The way of learning and performing practice, the tools and methods that are being used for it and the spaces that these processes take place are shifting with the change of information and technology. Under these circumstances architectural education has faced difficulties in being up to date in particular about curriculum, program and physical requirements. While instant solutions give instant results, it is inevitable that rooted solutions will be encountered to keep up with this rapid change. For this reason, countless “informal education” activities are being implemented, such as competitions, workshops, assemblies, forums, publications, etc. This paper focuses on BASS (Betonart Architectural Summer School) as a case to understand the motives of participating in such activities from the perspective of architectural students. It tries to demonstrate that students are aware of the importance of informal educational activities, furthermore they are increasingly demanding.